2010
DOI: 10.1021/ja105704m
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Enantioselective Synthesis of trans-1-Alkyl-2-substituted Cyclopropanes via Tandem Conjugate Addition−Intramolecular Enolate Trapping

Abstract: Cu-TolBINAP-catalyzed conjugate addition of Grignard reagents to 4-chloro-α,β-unsaturated esters, thioesters, and ketones leads to 4-chloro-3-alkyl-substituted thioesters and ketones in up to 84% yield and up to 96% ee upon protonation of the corresponding enolates at low temperature. Tandem conjugate addition-enolate trapping, however, yields trans-1-alkyl-2-substituted cyclopropanes in up to 92% yield and up to 98% ee. The versatility of this reaction is illustrated by the formation of key intermediates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 53 publications
0
38
0
1
Order By: Relevance
“…Binap-type atropoisomeric ligands were first evaluated. Initial experiments with Binap [11] highlighted the potential of Me 2 Zn in these reactions to achieve good conversions and 1,4-regioselectivity at room temperature, albeit with only modest enantioselectivities up to 26 %. Control experiments showed that both ligand and metal are essential:noc onversion could be observed in the absence of Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Binap-type atropoisomeric ligands were first evaluated. Initial experiments with Binap [11] highlighted the potential of Me 2 Zn in these reactions to achieve good conversions and 1,4-regioselectivity at room temperature, albeit with only modest enantioselectivities up to 26 %. Control experiments showed that both ligand and metal are essential:noc onversion could be observed in the absence of Scheme 1.…”
mentioning
confidence: 99%
“…Theu se of more reactive organometallic reagents such as Me 3 Al or MeMgBr [12] led only to racemic 1,4-product 2a or amixture of 1,2/1,4 adducts,respectively (see SI). When other atropoisomeric classical ligands such as tol-binap, [11] Segphos, [13] difluorphos, [14] and phosphoramidites [15] were used, unsatisfying enantioselectivities were observed that did not exceed 70 %. Higher selectivity was observed with Josiphos L1a [16] (87 % ee)w hereas less than 5% ee was observed with the structural isomer L1b (Scheme 2; Table 1, entries 1-3).…”
mentioning
confidence: 99%
“…[8] These enolates also open epoxides [9] or take part in cross-coupling [10] or cyclopropanation reactions. [11] Chiral metal enolates can also be trapped intramolecularly to form cycles. [12] This was realized by another conjugate addition [13] or a nucleophilic displacement of a remote halogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…[12] This was realized by another conjugate addition [13] or a nucleophilic displacement of a remote halogen atom. [11] Intramolecular enolate trapping is also useful for Rh-catalyzed additions, although these reactions typically run without a chiral ligand. [14] Hayashi developed an intermolecular enantioselective version of rhodium enolate trapping in the aldol reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the cyclopropane-containing subunit (Scheme 5) employed Feringa’s elegant asymmetric 1,4-addition protocol 12 as the key step. Conjugate addition of MeMgBr to chloro enone 14 , prepared in one step from allyl chloride and acetyl chloride, 13 in the presence of CuI and ( R )-tolylBINAP provided a chloro enolate that could either be warmed to generate cyclopropane 15 directly or quenched at low temperature and subjected to base to effect the cyclopropanation in >90% ee.…”
mentioning
confidence: 99%